'In fabrorum potestate': Plautus and the Mother's Power in Ancient Rome. Issue 1 (2nd January 2018) - Roccia, Maria Elena
ABSTRACT: Plautus' Mostellaria contains the first attestation of the attribution of potestas over children to both parents, the mother as well as the father, in ancient Rome. Such an early analogy between pater and mater regarding their social status as parentes, along with a certain correlation between the parents' duties and their power over their children, seems to suggest that a new social conception of the Roman family was already spreading in Plautus' day, concurrently with the progressive recognition of natural kinship ( cognatio ). Set in the framework of the legal and literary sources on this matter, the excerpt brings under discussion the traditional motionless view of the patria potestas and appears to be particularly significant in reconstructing not only the real social and legal status of the Roman mater but also the historical development of the legal system in ancient Rome.